Actividad inhibitoria in vitro de hojas y fruto inmaduro de Inga edulis Mart. Y hojas de Laportea aestuans L. sobre α-glucosidasa - Iman Pezo, Luis David (2023)
The ethnopharmacological properties of Inga edulis Mart. (guaba) and Laportea aestuans L. (ishanga colorada), are considered within popular medicine in the Loreto region, whose main use is the empirical treatment of diabetes through infusions of leaves and other organs. The objective of this study was to determine the in vitro inhibitory activity of the leaves and immature fruit of I. edulis Mart. and leaves of L. aestuans L., by ultraviolet-visible spectroscopy (UV-vis) on ?-glucosidase using p-Nitrophenyl-?-D-glucopyranoside (p-NFGP) as substrate. The results of the extract of leaves of I. edulis Mart. at 1000 ?g/mL it showed a 46.86% percentage of inhibition on ?-glucosidase; the extract of immature fruit of I. edulis Mart. 17.50% and the leaves of L. aestuans L. 19.72%. The IC50>1000 ?g obtained for all the extracts evaluated allow us to conclude that none of them can be considered active, since concentrations higher than those evaluated are required to have an effect on ?-glucosidase.